Thermal, microstructural, and spectroscopic analysis of Ca2+ alginate/clay nanocomposite hydrogel beads - da Silva Fernandes, Renan [UNESP]; de Moura, Márcia Regina [UNESP]; Glenn, Greg M.; Aouada, Fauze Ahmad [UNESP] (Elsevier, 2018)
Polymeric hydrogels are important biomaterials with potential for various applications including the controlled release of drugs. Clay and zeolite nanostructures can enhance the absorption and release properties of hydrogels. In our previous work, a procedure was optimized for making hydrogel beads. The objectives of this study were to use the optimized bead forming procedure to prepare clay and zeolite nanocomposite hydrogel beads and characterize their microstructure, thermal and chemical properties. The hydrogels were prepared by dripping solutions of either sodium alginate or sodium alginate/nanostructure (clay and/or zeolite) into beakers containing different concentrations of CaCl2 at 25 °C. Fourier transform infrared spectroscopy (FTIR) analysis detected the presence of functional groups associated with alginate, clay and zeolite. The microstructure of the alginate beads was somewhat rough with small protrusions. Flakes were visible in micrographs of beads containing nanoclay. The elemental composition of the hydrogels was investigated by energy dispersive X-ray spectrometry (EDX). EDX spectra revealed magnesium, sodium, aluminum, silicon and increased the levels of oxygen in the nanoclay compositions. The incorporation of nanoclays decreased the percentage of organic matter lost as detected by thermogravimetric analysis (TG). TG was also able to detect the incorporation of nanoclay in hydrogels. The nanoclays proved to be more effective than zeolites in producing alginate hydrogels with satisfactory swelling characteristics.
Keywords: Hydrogels; Nanoclay; Nanocomposites; Sodium alginate; Zeolite